Demanda e cuidados em saúde mental: um estudo com profissionais da atenção psicossocial e da saúde da família - Gonçalves, Rafael Camilo (2020)
The implementation of the Psychosocial Care Network in 2011 in Brazil poses different points for the mental health care of users, therefore it is necessary to articulate the services that make up the network with each other and with equipment outside the health sector that are necessary for the attention to the person in a situation of psychological distress. For this study, the Psychosocial Care Center and the Family Health Strategy stand out in guiding and proposing care to this public. Thus, the main objective of this research was to identify the demand for mental health and care actions according to professionals from a Psychosocial Care Center team and two Family Health teams supported by a NASF-AB. The specific objectives were: (1) to investigate with the professionals who integrate the levels of primary and psychosocial care their understanding of practices and actions of promotion, prevention and treatment related to mental health and (2) to understand the forms of articulation of care used by primary care teams and psychosocial care. The present research is characterized as qualitative, descriptive and exploratory, it was carried out in a city in the interior of Minas Gerais with four psychologists and a nurse from a Psychosocial Care Center II and two psychologists, three nurses and nine community health agents from two Basic Family Health Units (UBSF) supported by a NASF-AB. Questionnaires and semi-structured interview scripts were used to produce the data. The results showed that CAPS professionals carry out activities such as reception, groups, elaboration of Singular Therapeutic Projects, team and intersectoral meetings. The concepts and practices of health promotion, prevention and treatment are very similar in the conception of CAPS professionals, which signaled that actions can be carried out in an isolated way. Regarding the UBSFs professionals, there was a greater occurrence, by the community health agents, of activities such as home visits, guidance and realization and updating of family registers. Nursing and psychology professionals performed actions such as reception, individual care, groups, workshops and meetings in the service and with other services. It was found in these units a logic of passing cases to specialized training professionals, as in the case of mental health, with hardly any joint discussion or shared responsibility among the service professionals. The UBSF professionals understood health promotion more linked to the proposals of groups and workshops, while they attributed prevention to the practices of guidance and the search for healthy ways of life. The treatment was almost exclusively linked to the curative aspects and the use of medications, although he was also reminded of other aspects that can contribute to it, such as family support and bond with the service and professionals. For each service, it was possible to create a figure that shows the user's flow through the unit. One can also perceive the occurrence of the articulation of these services with other services and among them, characterizing not only an intrasectoral service, but also an intersectoral one.